Factors affecting levels of circulating cell‐free fetal DNA in maternal plasma and their implications for noninvasive prenatal testing. (14th July 2015) - Kinnings, Sarah L.; Geis, Jennifer A.; Almasri, Eyad; Wang, Huiquan; Guan, Xiaojun; McCullough, Ron M.; Bombard, Allan T.; Saldivar, Juan‐Sebastian; Oeth, Paul; Deciu, Cosmin
<x xml:space="preserve">Abstract</x> What's already known about this topic? Sufficient fetal‐to‐total DNA fraction ('fetal fraction') of a maternal plasma sample is required for accurate aneuploidy detection via noninvasive prenatal testing. Fetal fraction increases with gestational age and decreases with maternal weight, which also increases with gestational age. When compared with euploid samples, an overall increase in fetal fraction in T21‐positive samples and a decrease in fetal fraction in T18‐positive and T13‐positive samples is observed. What does this study add? This is the largest known study size from which to assess the effects of maternal and fetal factors on the fetal fraction. The effects of maternal weight, body mass index, and blood volume on fetal fraction are compared. The effect of fetal aneuploidy status on the fetal fraction is shown across different gestational ages. Multiple measurements of fetal fraction per patient are compared both from the same and different blood draws. © 2015 John Wiley & Sons, Ltd.